Use of Props During Mealtime for Children With Autism Spectrum Disorders: Self-Regulation and Reinforcement. (October 2018) - Muesbeck, Jessica; St. John, Brittany M.; Kant, Shannon; Ausderau, Karla K.
Mealtime is an important family routine commonly affected for families with children with autism spectrum disorders (ASD). Limited research is available regarding strategies families incorporate to support mealtime engagement. The purpose of this study was to explore the frequency and characterize the purpose of Props used during mealtimes with children with ASD. A total of 12 families with a child(ren), N = 14, aged 2 to 7 years, with ASD and mealtime challenges or eating difficulties participated in video-recorded mealtimes in their home. Independent coders analyzed mealtimes for the frequency and purpose of Props (items used to support child participation during mealtime). Props were used by 75% of families ( n = 9); common Props included toys, electronics, and books. Props were used primarily as a self-regulation tool for the child and occasionally as positive reinforcement for specific behaviors. Overall, Props were used to support child engagement in mealtime. Occupational therapists should consider using Props as individualized, accessible, and supportive mealtime interventions for families and children.